Case Report: Adverse reaction to butorphanol in a Collie homozygous for the ABCB1-1∆ (MDR1) mutation - Nelson, Tyler S.; Allen, Heather N.; Hardison, April; Miscioscia, Erin; Khanna, Rajesh; Maxwell, Elizabeth A. (Frontiers in Veterinary Science, 2025)
Certain dog breeds, particularly herding breeds like Collies, are predisposed to drug sensitivity due to the ABCB1-1∆ (previously known as MDR1) mutation, which disrupts P-glycoprotein (P-gp) function. This mutation impairs drug efflux at the blood–brain barrier, leading to increased susceptibility to neurotoxic effects. While adverse reactions to P-gp substrate drugs such as macrocyclic lactones and chemotherapeutics are well documented, opioid sensitivity remains poorly understood. This case report documents a Collie that developed severe neurotoxicity, including profound sedation, ataxia, hypersalivation, and seizures, following a single 0.2 mg/kg dose of butorphanol. Symptoms persisted despite supportive care, requiring continuous naloxone administration for approximately 40 h before significant improvement. Neurotoxicological effects may have been exacerbated by metoclopramide and maropitant, known P-gp substrates. This case underscores the need for further research into opioid pharmacokinetics in ABCB1-1∆ mutant dogs and highlights the importance of genetic screening in veterinary practice. To enhance patient safety, integration of automated alerts within electronic medical record systems is recommended to flag high-risk drugs for at-risk breeds, providing real-time warnings, dosing adjustments, and monitoring guidance. These measures could reduce adverse drug reactions and improve clinical outcomes in genetically susceptible dogs.